The Effect of Awareness and Attitude on Preferences For Islamic Banks and Conventional Banks: The Role of Religiosity of Ethnic Muslim Customers Sasambo - Taufiq Chaidir; Yasin, Muaidy; Jalaludin, Jalaludin; Wahyunadi, Wahyunadi (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
The purpose of this study is to show the role of religiosity (extrinsic and intrinsic factors) in awareness and attitudes, as well as its influence on the preference of Islamic banks over conventional banks among Muslim SASAMBO (Sasak-Samawa-Mbojo) ethnicity customers in West Nusa Tenggara Province. The research method used is explanatory. The study used non-probability sampling techniques, specifically the judgment sampling method. The sample size was 120 customers, with 40 from each ethnicity. PLS-SEM (Partial Least Square-Structural Equations Modelling) is the analysis model used in this study to obtain estimation results and test hypotheses. The findings indicate that extrinsic religiosity significantly impacts awareness but does not affect attitudes. Intrinsic religiosity has a significant impact on awareness. In the second factor, intrinsic religiosity had no significant influence on attitudes. The awareness aspect has significantly impacted customer preferences for Islamic banks over conventional banks. The attitude aspect has been shown to have no significant effect on customer preferences for Islamic banks as opposed to conventional banks. Customers who understand the concepts of traditional and Islamic banking can better determine which products and systems are suitable and which are not. However, when customers become aware of these products and services, most show interest in using traditional and Islamic financial transaction methods.